2015
DOI: 10.14348/molcells.2015.2146
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-576-3p Inhibits Proliferation in Bladder Cancer Cells by Targeting Cyclin D1

Abstract: MicroRNAs (miRNAs) are small, endogenous RNAs that play important gene-regulatory roles by binding to the imperfectly complementary sequences at the 3-UTR of mRNAs and directing their gene expression. Here, we first discovered that miR-576-3p was down-regulated in human bladder cancer cell lines compared with the non-malignant cell line. To better characterize the role of miR-576-3p in bladder cancer cells, we over-expressed or down-regulated miR-576-3p in bladder cancer cells by transfecting with chemically … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
38
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 39 publications
(40 citation statements)
references
References 32 publications
(31 reference statements)
2
38
0
Order By: Relevance
“…in BCa have been identified. 9,33 In our research, we found that miR-502-5p could regulate cell proliferation by targeting CCND1…”
Section: Discussionmentioning
confidence: 62%
See 2 more Smart Citations
“…in BCa have been identified. 9,33 In our research, we found that miR-502-5p could regulate cell proliferation by targeting CCND1…”
Section: Discussionmentioning
confidence: 62%
“…Previous work has shown that CCND1 plays a key role in regulating the cell cycle of BCa cells, 9 and downregulation of CCND1 induced revealed that the expression of CCND1 was markedly reduced in bladder cancer ( Figure S3G). Consequently, CCND1, targeted by miR-502-5p, can regulate cell proliferation in BCa cells.…”
Section: Ccnd1 Acts As a Target Of Mir-502-5p In Regulating The Celmentioning
confidence: 79%
See 1 more Smart Citation
“…Emerging discoveries of disordered miRNAs have been reported to accelerate the progression and metastasis of cancer, including BCa. Our team has previously identified a series of miRNAs, including miR-26a, miR-101, miR-124-3p, miR-320c, miR-409-3p, miR-490-5p, miR-576-3p, miR-433, miR-148a and miR-323a-3p, involved in the progression of BCa [9][10][11][12][13][14][15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…5, 6 In our previous studies, we identified a series of miRNAs involved in bladder cancer proliferation, migration and invasion, including miR-26a, miR-101, miR-124-3p, miR-320c, miR-409-3p, miR-490-5p, miR-433 and miR-576-3p. 7, 8, 9, 10, 11, 12, 13, 14 However, the biological function of miRNAs in bladder cancer is still unclear.…”
mentioning
confidence: 99%